Lung transplant recipient attitudes and beliefs on accepting an organ that is positive for hepatitis C virus. Issue 4 (12th July 2021) - Humar, Sapna S.; Pinzon, Natalia; Cypel, Marcelo; Abbey, Susan
Abstract: Introduction: Little is known about patient perceptions regarding HCV+ organ use in non‐HCV‐infected recipients. This study examined factors influencing the decision to accept HCV+ organs and the resulting impacts. Methods: Adult lung transplant (LT) patients or candidates who had consented to receive an HCV+ organ completed a survey including multiple choice, a five‐point Likert scale, and free‐text answers. A total of 67 LT recipients or candidates who had consented to receive HCV+ organs were enrolled, of which 21/67 (31%) received HCV+ lungs, 39 (58%) HCV− lungs, and seven (10%) were still waiting. Results: Pre‐transplant, 50/67 (75%) patients felt it was either "completely safe" or "very safe" to accept an HCV+ organ. Although 22/67 (33%) said they never or rarely took risks, they still made the decision to accept an HCV+ organ. Common reported reasons were desperation, perception of having "no choice, " and increasing symptom severity. In the subset of patients that were transplanted with an HCV+ organ ( n = 21), only 12.5% reported second thoughts about accepting. Post‐transplant, the majority (87.5%) never felt any anxiety about HCV and most (83%) reported no impact from HCV. Perception of treatment tolerability and ease was highly favorable. Conclusion: Use of HCV+ organs demonstrated minimal detrimental perceived impacts on lung transplant patients. Patients generally found the experience to be very positive.